The significance of focal pattern in hypsarrhythmia - Anna Wiedemann; Birgit Stark; Gudrun Gröppel (Brain Disorders)
Introduction: Infantile Epileptic Spasms Syndrome (IESS) presents a therapeutic challenge and is frequently associated with developmental delay. It is characterized by seizures and hypsarrhythmia on the EEG and has multiple etiologies that influence therapeutic decisions. Severity of hypsarrhythmia serves as an indicator for evaluating treatment efficacy. However, the correlation between clinical symptoms, EEG patterns, and cerebral lesions requires further investigation. Methods: Eighteen infants diagnosed with IESS underwent video-EEG monitoring and MRI. Hypsarrhythmia severity was assessed using the Kramer et al. scoring system. Clinical semiology was evaluated for lateralizing features. Statistical analyses were conducted to examine correlations between EEG findings, clinical symptoms, and cerebral lesions. Results: All infants exhibited hypsarrhythmia and 72.3 % presented with cerebral lesions, predominantly bilateral. Clinical symptoms frequently indicated lateralization, whereas EEG findings demonstrated lateralization in only 22.2 % of cases. No significant correlation was identified between hypsarrhythmia patterns and clinical symptoms or lesions. The severity of hypsarrhythmia was not a reliable predictor of the underlying etiology. Conclusion: This study found no association between hypsarrhythmic patterns and focal semiology or lesions. Given the heterogeneity of IESS, individualized diagnostic approaches remain essential. While the hypsarrhythmia score enhances the comparability of EEG patterns, its utility in determining the underlying etiology appears to be limited.